Evaluating growth and survival performance of G2 crossbreeds from two strains of bighead catfish (Clarias macrocephalus) : - Njihia, Dedan Karanja (Can Tho University, 2020)
The development of bighead catfish (C. macrocephalus) aquaculture in Vietnam has been constrained by the reduced growth performance in the domesticated strain. A study on the intra-specific hybridization of C. macrocephalus and its reciprocal crosses was carried out to evaluate their breeding and offspring growth and survival performance. Pure strains of C. macrocephalus (wild Ca Mau, CM, and domesticated Can Tho, CT) and their reciprocals were reproduced artificially through induced breeding whereby 6 mating combinations were generated. Results showed that pure domesticated strain (G0-CT) had a significantly higher fertilization rate (94.2%) and hatchability (80.1%) than the other groups (P<0.05). After 40 days of larval rearing, the two best-growth groups included ♀CM × ♂CT crossbreds (bodyweight of 1114.1 mg and length of 4.55cm) and pure crossbred line CTCM (1050 mg and 4.51cm, respectively), significantly different from the other groups. The CTCM group was recorded the highest survival rate (37.8%) while GO-CT was the lowest (27.2%); however, no difference was shown for survival performance (P>0.05). The outcome of the study showed heterosis in the crossbred CTCM and thus there is indeed the possibility of improving the growth and survival performance of bighead catfish in the Mekong Delta through intraspecific crossbreeding between CM and CT strains.